2020
DOI: 10.3389/fendo.2020.00630
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Alpha-Cells Contribute Together With Beta-Cells to CXCL10 Expression in Type 1 Diabetes

Abstract: C-X-C Motif Chemokine Ligand 10 (CXCL10) is a pro-inflammatory chemokine specifically recognized by the ligand receptor CXCR3 which is mostly expressed in T-lymphocytes. Although CXCL10 expression and secretion have been widely associated to pancreatic islets both in non-obese diabetic (NOD) mice and in human type 1 diabetic (T1D) donors, the specific expression pattern among pancreatic endocrine cell subtypes has not been clarified yet. Therefore, the purpose of this study was to shed light on the pancreatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 57 publications
4
20
0
Order By: Relevance
“…The increased colocalization rate between MDA5-glucagon and MDA5-insulin in T1D cases, possibly reflects ongoing inflammation of pancreatic islets particularly in recent onset cases. Of note, the strongest MDA5 increase was observed in β-cells of T1D DiViD case-3 which, among T1D DiViD donors, previously showed high level of insulitis alongside with a strong expression of HLA class-I molecules and several specific cytokines and chemokines (30,34,35). These results are in line with in-vitro studies showing that increased expression of MDA5 is also driven by pro-inflammatory molecules.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The increased colocalization rate between MDA5-glucagon and MDA5-insulin in T1D cases, possibly reflects ongoing inflammation of pancreatic islets particularly in recent onset cases. Of note, the strongest MDA5 increase was observed in β-cells of T1D DiViD case-3 which, among T1D DiViD donors, previously showed high level of insulitis alongside with a strong expression of HLA class-I molecules and several specific cytokines and chemokines (30,34,35). These results are in line with in-vitro studies showing that increased expression of MDA5 is also driven by pro-inflammatory molecules.…”
Section: Discussionsupporting
confidence: 86%
“…The colocalization rate of MDA5-glucagon and MDA5-insulin in non-diabetic controls was highly heterogenous both among islets of the same donor and among different donors; nevertheless the overall result showed a significant preferential localization in α-cells. Such heterogeneity was expected, based on previous findings on other molecules (30,31) and on other reports (32,33).…”
Section: Discussionsupporting
confidence: 78%
“…More recently, Nigi et al have shown CXCL10 expression in alpha cells and beta cells of donors with T1D. Interestingly, insulin-containing islets in T1D had an increased percentage of CXCL10-positive alpha cells compared to CXCL-10-positive beta cells suggesting an involvement of alpha cells in chemokine secretion (38). Both CXCL9 and CXCL10 have been shown to be secreted by beta cells in insulitic islets, which drive CXCR3+ autoreactive T cells to islets in the RIP-LCMV model of T1D.…”
Section: How Stressed Beta Cells Secrete Cytokines That May Be Involvmentioning
confidence: 97%
“…C-X-C motif chemokine ligand 10 (CXCL10) also called IP-10 (IFNg-induced protein 10) is a chemokine secreted by many cell types including monocytes, neutrophils, and endothelial cells (130,131). CXCL10 is increased in the serum and tissues of patients with various autoimmune diseases including T1D (99,132). Human islets, murine islets, and NIT-1 NOD beta-cells secrete CXCL10 when cultured with pro-inflammatory cytokines IL-1b and IFNg (127).…”
Section: Cxcl10mentioning
confidence: 99%